Factors influencing the recycling rate under the volume-based waste fee system in South Korea. (April 2018) - Park, Seejeen
Highlights: Examines the MSW recycling under the volume based waste fee system. The country of interest is the Republic of Korea (South Korea). Economic incentives and pro-environmental behavior affect recycling rate. MSW policy implementation as well as adoption should be investigated. Abstract: Since the early 2000s, the Republic of Korea (South Korea) has maintained its top-rank status for its municipal solid waste (MSW) recycling rate among OECD (Organization for Economic Cooperation and Development) member countries. The volume-based waste fee system (VWF) has been considered to be the major factor contributing to the high recycling performance, and extant research has verified the positive relationship between VWF adoption and the MSW recycling rate. Nevertheless, there exists a gap in the literature, as past research has focused more on testing the positive effects of VWF rather than on investigating the determinants of recycling rates after the adoption of VWF. The current study seeks to address this gap by investigating the various factors that affect recycling rates under the VWF system. More specifically, using data from 16 regions in South Korea over a period of 11 years, this study empirically tests the effects of VWF pricing, the citizen cost burden ratio for the VWF system, and pro-environmental behavior related to VWF on the recycling rate. The findings indicate that economic incentives such as cost savings on VWF plastic bag purchases and reduced burden from paying VWF expenses result in higher recycling rates. The findings also demonstrate that pro-environmental behavior in the VWF context positively affects the recycling rate.